Tingkat Pengetahuan Kader tentang Posyandu di Puskesmas Temindung Kota Samarinda - ola, Fransiska Keron Ola (Jurnal Kebidanan Mutiara Mahakam, 2020)
Community health workers are selected by the community from community members who are willing to voluntarily be able to help and have time to organize basic health service activities. The purpose of this study was to determine the level of knowledge community health workers in basic health service the health centers in Temindung, Samarinda. The research subjects of community health workers were 32 people who were on duty in basic health service activities in 10 basic health service centers in Temindung Samarinda. Measuring the level of knowledge of community health workers using a questionnaire. Percentage analysis to determine the level of knowledge about basic health service. Most community health workers are chosen directly with the essential requirements of being able to read, write and be friendly and voluntarily help and be in their community. Although their knowledge of basic health services is still low with 87.5% of basic health service. Knowledge of community health workers is still low Even though their knowledge is lacking, they still do health services at basic health services once a month. Basic health services are an important part of health services in the community, especially helping health workers in public health services to the community, but so they are expected to get training in basic health services to improve the Indonesian health republic's work program